Interview 11 - Simone A. James Alexander (Turkish Journal of Diaspora Studies, 2021)
The proliferation of the practices of diaspora runs parallel to transnational encounters and exchanges. While displacements and dispersals remain foundational to the formation of diasporas and diasporic communities, migrations and migratory experiences have resulted in the continued evolution of the concept of diaspora to suit the needs and demands of ever-changing im/migrant communities. This flexibility and adaptability of diaspora accommodate the exchange of goods and services, for example, remittances, the transfer of funds by migrants to their home countries, which has become one of the largest financial inflows to these receiving countries.